Interspecific transfer of parasites following a range-shift in Ficedula flycatchers - Jones W. (John Wiley and Sons Ltd, 2022)
Human‐induced climate change is expected to cause major biotic changes in species distributions and thereby including escalation of novel host‐parasite associations. Closely related host species that come into secondary contact are especially likely to exchange parasites and pathogens. Both the Enemy Release Hypothesis (where invading hosts escape their original parasites) and the Novel Weapon Hypothesis (where invading hosts bring new parasites that have detrimental effects on native hosts) predict that the local host will be most likely to experience a disadvantage. However, few studies evaluate the occurrence of interspecific parasite transfer by performing wide‐scale geographic sampling of pathogen lineages, both within and far from host contact zones. In this study, we investigate how haemosporidian (avian malaria) prevalence and lineage diversity vary in two, closely related species of passerine birds; the pied flycatcher Ficedula hypoleuca and the collared flycatcher F. albicollis in both allopatry and sympatry. We find that host species is generally a better predictor of parasite diversity than location, but both prevalence and diversity of parasites vary widely among populations of the same bird species. We also find a limited and unidirectional transfer of parasites from pied flycatchers to collared flycatchers in a recent contact zone. This study therefore rejects both the Enemy Release Hypothesis and the Novel Weapon Hypothesis and highlights the complexity and importance of studying host‐parasite relationships in an era of global climate change and species range shifts.